THE IMPACT OF SURROUNDINGS ON THE CHARACTERS IN THOMAS HARDYâS NOVELS - Rahman, Suzana; Muntiningsih, Ratna (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2016)
Abstract The THE IMPACT OF SURROUNDINGS ON THE CHARACTERS IN THOMAS HARDYâS NOVELSâ is to apply the writersâ knowledge on literature and to show their interest in reading novels. The writers transfered not only their limited knowledge in analysing novels as literary works but also building the awareness of the importance of reading habit to their students of Unswagati because all of them take the subject of Introduction to English Literature. Reading and analyzing novel is really beneficial for students that both can improve the students reading skill but also their English ability, moreover, they will have the ability in criticizing the novel from different views. In brief, it will also improve their critical thinking. Afterwards, by describing the characters and their attitudes toward each other and how the surroundings influence them, we also learn about their culture. The theory that is used in analysing those novels is from Harvey, Murphy, Klarer, and Lodge. The method that is applied in analysing the characters and the surroundings is descriptive qualiative in which the writers take the data by reading the three novels, explain in details about the characters and the surroundings involved in the story and some other elements supported the completeness of the story. Key words: surroundings, impact, literary